Fabrication of MnOx heterogeneous catalysts from wet sludge for degradation of azo dyes by activated peroxymonosulfate. Issue 16 (27th January 2015) - Xu, Lili; Liu, Wanpeng; Li, Xingfa; Rashid, Sadia; Shen, Chensi; Wen, Yuezhong
Abstract : For dewatering and resource utilization of sewage sludge, we proposed a strategy that integrates wet sludge treatment with catalyst preparation and heavy metals in catalysts have been solidified in catalysts to prevent their leaching into solution. Abstract : For dewatering and resource utilization of sewage sludge, catalyst preparation paralleled with sewage sludge dewatering, was explored. In order to obtain a better understanding of this strategy, an anaerobic sludge based MnO x catalyst (MnO x /HCAS) was characterized, and tested in activation of Oxone for dye degradation in aqueous solution. The multi-valence oxidation states of manganese were formed in MnO x /HCAS. The catalyst exhibits high catalytic activity towards Oxone for the degradation of dyes in aqueous solution. The kinetic data followed first order kinetics with an activation energy of 21.87 kJ mol −1 . The evaluation of the reusability of MnO x /HCAS showed that MnO x /HCAS exhibited high stability in recycled tests without losing its activity. The removal of a variety of anionic dyes also demonstrates an excellent catalytic performance of MnO x /HCAS. To investigate stabilization of heavy metals in the catalyst, a leaching test was conducted, and the result showed that heavy metals can be solidified to prevent their leaching into solution. The effect of different kinds of wet sludge was investigated. And all these sludge based MnO x catalysts exhibit good catalytic performance with azo dyes with degradation rates more than 98%, which decides its unquestionable possibility for fabrication of MnO x heterogeneous catalysts from wet sludge and its practical applications.